PERAN BALAI PENYULUHAN PERTANIAN SEBAGAI PUSAT DATA INFORMASI PERTANIAN DALAM MENDUKUNG PROGRAM KOSTRATANI - Tience Elizabet Pakpahan; Makruf Wicaksono; Qorimah Handari Hrp (JURNAL AGRIBISNIS TERPADU, 2021)
This research is entitled The role of the Agricultural Extension Office as an Agricultural Information Data Center in supporting the Kostratani Program in Namo Rambe Sub-District, Deli serdang Regency, North Sumatra Province. The purpose of this study is to know the level of role of the Extension Office and the influcing factors as an agricultural information data center in supporting the Kostratani program. This research was conducted in Namo Rambe Sub-District, Deli Serdang Regency in March to July 2020. Data collection methods are observations and interviews using questionnaire instruments that have been tested for validity and reliability, while data analysis methods use likert scale and multiple linear regression. The results of the study showed that the level of role of the Agricultural Extension Center (BPP) as an agricultural information data center in supporting the Kostratani program in Namo Rambe sub-district belongs to a very high category of 83.44%, while linear regression results against factors affecting the role (BPP) as agricultural information data centers are obtained equations as follows Y = 4.98 2 + 0.032X1 + 0.522X2 + 0.454X3 – 0.098X4 + 0.200X5 + 0.390X6 + 0.392X7 + 0.079X8. Further tests using t-count showed that factors that had a significant effect on the role of the Agricultural Counseling Center (BPP) of agricultural information data centers were the role of counselors (2,766), institutional (2,240), IT personnel /experts (2,361), and farmer participation (2,217).